Eating behavior of teachers as a reflection of their level of competence in matters of a healthy lifestyle - Natalia I. Kadochnikova; Natalia L. Dyomina (Siberian Journal of Life Sciences and Agriculture)
At present, the problems of the formation of a way of life and the organization of education that contribute to the formation and preservation of health are of particular relevance. The professional activity of a teacher consists not only of a conscious active influence on students, but the personality of the teacher himself also has an unconscious influence, being a kind of model of behavior. Thus, having an educational impact on the younger generation. The tasks of protecting and promoting the health of students can be successfully solved only if the teacher himself/herself is healthy and lives a healthy lifestyle. Unfortunately, the presence of an individual’s theoretical knowledge in the field of healthy lifestyle culture does not guarantee his/her self-preservative behavior by no means.